Students’ Motivation and Perception in Reading English Texts - LumbanTobing, Tessalonika; Munthe, Melisa Debora; Br. Aritonang, Sintia Romian; Asyari, Sarah; Hulu, Novia Magdalena; Br Sembiring, Yenita; Lumbanbatu, Ira Maria Frans (SIGEH ELT : Journal of Literature and Linguistics, 2024)
This study was aimed to investigate Students’ Motivation and Perception in Reading English Texts. This study was conducted to find out (1) what intrinsic factors influence students' motivation to read English texts, (2)what extrinsic factors influence students' motivation to read English texts, (3)what differences exist in reading motivation among students of different demographic backgrounds and (4) how does motivation to read English texts vary across different age groups, gender, and socio-economic status. This study used descriptive qualitative as the research design. It was conducted to the students of SMK Telkom 2 Medan. After analyzing the data, it was found that students’ motivation and perception in reading English texts are influenced by a combination of intrinsic and extrinsic factors, educational environment, and personal attitudes towards reading. By understanding these factors, educators can implement strategies to enhance motivation and foster positive perceptions, ultimately improving students' reading skills and their overall learning experience